Tax Design for Inclusive Economic Growth - Brys, Bert (OECD Publishing, 2016)
This paper examines how the design features of countries' tax systems can be strengthened to support inclusive economic growth. In the context of the OECD's New Approaches to Economic Challenges (NAEC) initiative, this paper seeks to re-assess the policy recommendations stemming from the 2008 Tax and Economic Growth report, which focused on the impact of taxes on economic growth from an efficiency perspective, to more explicitly take account of equity considerations. Drawing on recent developments in the academic literature and in countries' tax policies, the paper examines how the basic design aspects of each tax can be improved to better achieve inclusive growth. It also looks at how the interactions of taxes with other factors - both within and beyond tax systems - affect their efficiency and equity outcomes. The paper more generally emphasises the need to look at tax and benefit systems as a whole to fully assess the efficiency and equity implications of tax policies. The inclusive design of domestic tax policies needs to go hand in hand with the implementation of international tax rules and mechanisms that prevent tax evasion and tax avoidance. It also requires measures that strengthen the functioning of the tax administration and incentivise agents to operate within the formal economy. The paper lays the groundwork for future empirical work to support tax design for inclusive growth
Keywords: Taxation; Economics